The Contribution of Forensic Psychology to Improve the Protection of Rape Victims in Trials - Patisina; Antonius Maria Laot Kian; Benedictus Renny See (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to identify the contribution of forensic psychology in the preparation of rape victims to testify in court and analyze the legal framework applicable to the protection of rape victims in the legal system in Indonesia. This research is normative juridical by using secondary data such as laws and regulations, literature studies, and expert interviews of Forensic Psychologists. The results of the first research analysis of forensic psychology contribute to the preparation and recovery of rape victims in the context of trials. By taking into account regulations such as Law Number 18 of 2014 concerning Mental Health and Regulation of the Minister of Health of the Republic of Indonesia Number 45 of 2017, the practice of forensic psychology in Indonesia is directed to improve practice standards and protect the public from unethical practices. Second, legal protection for rape victims in Indonesia consists of two main aspects, namely preventive and curative protection. Preventive protection is established through regulations such as Law Number 1 of 2023 concerning rape in the Criminal Code and Law Number 12 of 2022 concerning Sexual Violence (TPKS Law), which guarantees fair and comprehensive treatment and holistic recovery for victims. Curative legal protection is regulated by Law Number 36 of 2009 Article 144, which emphasizes treatment and rehabilitation approaches for victims after the commission of crimes.